Analisis Das Sollen dan Das Sein dalam Penerapan Prinsip Good Corporate Governance pada Perseroan Terbatas di Indonesia. - Permadi, Adi; Aolia, Alfi Muhammad; Shahibul Hikam, Muhammad Athaillah; Husni, Asep; Najmudin, Nandang (Public Sphere: Jurnal Sosial Politik, Pemerintahan dan Hukum, 2026)
The principle of Good Corporate Governance (GCG) serves as a fundamental pillar in the management of Limited Liability Companies in ensuring transparency, accountability, and alignment with the interests of shareholders and stakeholders. In practice, however, the implementation of GCG often encounters a gap between das sollen the normative standards stipulated in the Company Law and GCG guidelines and das sein, which reflects the actual behavior of corporate organs, particularly the board of directors. This study aims to examine legally how the discrepancy between das sollen and das sein emerges in the application of GCG principles, and how such discrepancies affect the legal accountability of directors. This research employs a normative juridical method using a statutory approach, a conceptual approach, and case analysis based on relevant Supreme Court decisions. The analysis of decisions such as Supreme Court Decisions No. 374 K/Pdt/2012, No. 297 K/Pdt.Sus/2012, and No. 39 PK/Pdt.Sus-Pailit/2013 shows that directors may be held liable when proven to have exceeded their authority, acted negligently, or failed to fulfill their fiduciary duties as mandated under Article 97(3) and Article 98 of the Company Law. The findings indicate that deviations from GCG implementation arise due to weak internal oversight mechanisms, a lack of transparency in managerial decisions, and the persistent occurrence of conflicts of interest in corporate decision-making processes. These discrepancies lead to an increased risk of corporate losses and may result in personal liability for directors, whether through civil lawsuits or corporate legal accountability. Judicial enforcement through court decisions reinforces that GCG is not merely ethical guidance, but a binding normative standard with legal consequences. Thus, this study emphasizes that harmonizing das sollen and das sein is essential for the effective implementation of GCG in Indonesia. Strengthening regulations, improving oversight by corporate organs, and ensuring consistent law enforcement are crucial to achieving governance practices that comply with the prevailing legal standards.ABSTRAKPenelitian ini menganalisis efektivitas Badan Penyelesaian Sengketa Konsumen (BPSK) dalam memberikan akses keadilan bagi konsumen melalui pendekatan yuridis-empiris yang memadukan wawancara semi-terstruktur dengan pemangku kepentingan BPSK Kota Bandung, observasi proses penyelesaian, serta kajian regulasi yang mendasari berdirinya lembaga tersebut. Berdasarkan Perpres Nomor 90 Tahun 2001, BPSK berperan sebagai lembaga non-litigasi yang menyelesaikan sengketa antara konsumen dan pelaku usaha melalui konsiliasi, mediasi, dan arbitrase, serta berwenang menjatuhkan sanksi administratif kepada pelaku usaha yang melanggar. Temuan menunjukkan bahwa struktur keanggotaan majelis yang terdiri atas unsur pemerintah, pelaku usaha, dan konsumen dengan proporsi seimbang merupakan instrumen imparsialitas dalam proses ajudikasi sengketa. Namun, efektivitas layanan BPSK masih menghadapi sejumlah tantangan: keterbatasan cakupan kelembagaan karena belum seluruh kabupaten/ kota memiliki BPSK sehingga menimbulkan beban perkara terpusat serta potensi hambatan akses bagi konsumen dari wilayah pinggiran; prosedur pembuktian yang masih konvensional; dan ketergantungan penyelesaian pada itikad baik pelaku usaha dalam menjalankan putusan. Meski demikian, BPSK berhasil berperan sebagai garda awal perlindungan hukum sebelum sengketa meningkat ke ranah litigasi, dengan mekanisme mediasi tetap menjadi pilihan dominan dan memperkuat asas keadilan prosedural bagi para pihak. Penelitian ini memberikan kontribusi empiris dalam memahami posisi BPSK sebagai bagian dari arsitektur alternatif penyelesaian sengketa di Indonesia serta membuka ruang evaluasi terhadap urgensi peningkatan digitalisasi proses dan perluasan kelembagaan menuju efektivitas yang lebih optimal di masa mendatang.